2011
DOI: 10.1111/j.1540-8159.2011.03200.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Hospitalization Is Not Increased with Short‐Term Elevations in Exposure to Fine Particulate Air Pollution

Abstract: Unlike previously observed associations with ischemic heart disease events and heart failure hospitalizations using similar study design and approaches, this study found that hospitalization for AF was not significantly associated with elevations in short-term exposure to fine PM air pollution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
1
36
1
1
Order By: Relevance
“…Researchers have reported alterations in heart-rate intervals associated with variations in ambient levels of air pollution, particularly in individuals with high levels of markers of oxidative stress and systemic inflammation. 92 However, pollutant-induced ventricular arrhythmia 90,93 and atrial fibrillation 50,94 have been predominantly detected in people with existing cardiac disease. In addition, the results of controlled-inhalation studies have shown no short-term risk of arrhythmia in healthy adults, suggesting that the association between pollution and the risk of cardiac rhythm disturbances is limited to highly susceptible individuals.…”
Section: Blood Pressure and Vascular Functionmentioning
confidence: 99%
“…Researchers have reported alterations in heart-rate intervals associated with variations in ambient levels of air pollution, particularly in individuals with high levels of markers of oxidative stress and systemic inflammation. 92 However, pollutant-induced ventricular arrhythmia 90,93 and atrial fibrillation 50,94 have been predominantly detected in people with existing cardiac disease. In addition, the results of controlled-inhalation studies have shown no short-term risk of arrhythmia in healthy adults, suggesting that the association between pollution and the risk of cardiac rhythm disturbances is limited to highly susceptible individuals.…”
Section: Blood Pressure and Vascular Functionmentioning
confidence: 99%
“…Likewise, epidemiological studies have failed to show a relationship between permanently higher fine particle ex-posure and AF incidence 158,159 (Table 8). Short-term exposure may directly enhance AF susceptibility in patients with cardiac disease.…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with coronary heart disease and elderly participants, increasing exposure to PM air pollution increased the incidence of asymptomatic runs of supraventricular arrhythmias in two observational studies (Berger et al 2006; Sarnat et al 2006). However, in a recent robust case-crossover study of > 10,000 admissions to hospital with AF, there was no association with PM air pollution (Bunch et al 2011). A more recent prospective analysis of patients with implantable cardiac defibrillators with established cardiac disease showed an increased risk of AF with acute increases in exposure to PM air pollution (Link et al 2013).…”
Section: Discussionmentioning
confidence: 99%